A case of acute hypogonadism following taipan (Oxyuranus scutellatus) envenomation. (June 2020) - Van Der Meer, Ebonney; Conway, Luke; Little, Mark; Hanson, Josh
Abstract: A previously well man developed acute, marked tender bilateral gynaecomastia two months after confirmed taipan ( Oxyuranus scutellatus ) envenomation. He had had laboratory evidence of thrombotic microangiopathy (TMA) including microangiopathic haemolytic anaemia, thrombocytopenia and acute kidney injury. Scrotal ultrasound revealed bilateral testicular atrophy, his serum testosterone was repeatedly low, while his luteinising and follicle stimulating hormone were elevated. It is hypothesised that TMA-related testicular ischaemia was responsible for his primary gonadal failure and dramatic clinical presentation. Highlights: Taipan envenomation is uncommon, and its complications are incompletely defined. Reports of endocrine complications after snakebites are infrequent. Thrombotic microangiopathy can occur with taipan envenomation. Thrombotic microangiopathy classically affects the kidneys but can affect any organ. TMA-related end-organ injury may result in delayed clinical presentations.